Body Image Perception and Its Association with Food Intake among Undergraduate Students in Kuala Lumpur, Malaysia - Loke Sin Mun, Christie; Rajikan, Roslee; Yahya, Hanis Mastura (Makara Journal of Health Research, 2022)
Background: Body image dissatisfaction may lead to the practice of imbalanced diet to achieve the desired body weight. This study aimed to determine the association between body image perception and food intake among undergraduate students. Methods: This cross-sectional study was conducted on the data of 155 students from three faculties located at National University of Malaysia, Kuala Lumpur. Assessments included demographic data, body mass index, Contour Drawing Rating Scale, and 3-day food records. Results: The majority of the subjects were categorized as normal weight (64.5%), and the remaining were classified as underweight (26.5%), overweight (7.7%), and obese (1.3%). Body image dissatisfaction was observed in 80.6% of men and 87.9% of women. The majority of male subjects desired a large body, and the female subjects wanted a thin body. Body image dissatisfaction differed among the body mass index categories for both genders (p < 0.05). The mean intake of energy, potassium, calcium, thiamine, folate, vitamin A, vitamin D, vitamin E, vitamin B12, vitamin K, magnesium, and copper intake among the participants was below the recommended amount. Body image dissatisfaction was negatively correlated with calorie intake (r = −0.164, p < 0.05). Conclusions: The perception of having a large body size is associated with low-calorie intake among university students. Nutrition education programs are warranted to ensure healthy and balanced eating practices in this population.